(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose: Changes in the liver function tests (LFTs) are a serious complication during pregnancy and require proper analysis in order to avoid the risk factors in the diagnosis. Pregnancy-specific diseases are the most common reason for abnormal liver function tests while pregnant, especially in the third trimester. Materials and Methods: In this review article, pregnancy-related liver disease articles indexed in various databases were used. The collection of articles was evaluated by using keywords including liver diseases, pregnancy, eclampsia, fatty liver, liver enzymes and puerperium stage. Results: Liver cirrhosis, autoimmune infections, primary biliary redness, Wilson’s unwellness are few examples of pre-existing liver diseases which are exceptionally rare because pregnant women are often young and healthy. Intrahepatic cholestasis of pregnancy, the HELLP syndrome (haemolysis, increased liver enzymes, low platelets), eclampsia and acute fatty liver are all liver conditions that are specific to pregnancy. These abnormalities may cause foetal distress, serious liver damage, and even hepatic failure; as a result, rapid diagnosis and treatment are required. Serum transaminases, alkaline phosphatase, bilirubin etc. are frequently used diagnostic procedures. Conclusion: This review mainly focuses on the pregnancy-associated liver disorders with several biochemical tests, and their pathophysiology to interpret the abnormal condition of the liver during pregnancy. It also highlights the current scenario of Maternal Mortality Ratio in India. The effects of alcohol on unsuccessful pregnancies in females are also discussed. In this, so far bleak situation, changes in lifestyle, early and timely collaborative care by the obstetric and medical teams can produce the best results.